Let us solve the differential equation "y'= \\frac{x\u00b2+y\u00b2}{2xy}".
Let "y=ux". Then "y'=u'x+u". Consequently we have the following differential equation:
"u'x+u=\\frac{x\u00b2+u\u00b2x^2}{2ux^2}=\\frac{1+u\u00b2}{2u}"
"u'x=\\frac{1+u\u00b2}{2u}-u=\\frac{1-u\u00b2}{2u}"
"\\frac{du}{dx}x=\\frac{1-u\u00b2}{2u}"
"\\frac{2udu}{1-u^2}=\\frac{dx}{x}"
"\\int\\frac{2udu}{1-u^2}=\\int\\frac{dx}{x}"
"-\\int\\frac{d(1-u^2)}{1-u^2}=\\int\\frac{dx}{x}"
"-\\ln|1-u^2|=\\ln|x|-\\ln|C|"
"\\ln|C|=\\ln|x(1-u^2)|"
"C=x(1-u^2)"
"C=x(1-\\frac{y^2}{x^2})"
Therefore, the solution of the differential equation "y'= \\frac{x\u00b2+y\u00b2}{2xy}" is the following:
"C=x-\\frac{y^2}{x}"
Comments
Leave a comment